1992
DOI: 10.1021/bi00139a026
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of flexible analogs of N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine and of N-methyl-4-phenylpyridinium with highly purified monoamine oxidase A and B

Abstract: Sixteen analogs of N-methyl-1,2,3,6-tetrahydropyridine (MPTP) of varying degrees of flexibility have been studied as substrates of highly purified monoamine oxidases (MAO) A and B. The relative effectiveness of the various tetrahydropyridines as substrates of MAO A and B were evaluated in terms of the function turnover number/Km, as determined by initial rate measurements. The insertion of a methylene bridge between the phenyl and tetrahydropyridine moieties of MPTP to yield N-methyl-4-benzyl-1,2,3,6-tetrahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Compari son of the molds has shown that it is larger in MAO A than in MAO B (Figs. 1c, 1d); the latter well corre sponded to the literature data [22,27,28].…”
Section: The First Analysis Of Relationship Between Inhibitory Activisupporting
confidence: 85%
See 1 more Smart Citation
“…Compari son of the molds has shown that it is larger in MAO A than in MAO B (Figs. 1c, 1d); the latter well corre sponded to the literature data [22,27,28].…”
Section: The First Analysis Of Relationship Between Inhibitory Activisupporting
confidence: 85%
“…1). This assumption was consistent with data from other laboratories [22,23]. This obser vation we later used to formulate an important requirement to the compounds employed for such kind of research: adequate modeling of the active site of MAO can be carried out only with the use of revers ible competitive inhibitors of MAO characterized by preferentially "rigid" (with limited conformational mobility) structure and a limited set of conformers.…”
Section: The First Analysis Of Relationship Between Inhibitory Activisupporting
confidence: 77%
“…H NMR (DMSO-d6) δ 9.5 (bs, 2H, HCl), 8.89 (d, J ) 5.8, 2H, ArH), 8.07(d, J ) 6.0, 2H, ArH),6.94 (bs, 1H, NCH2CH), 3.94-4.15 (m, 2H, NCH2-CH), 3.33-3.66 (m, 2H, NCH2CH2), 2.42-2.46 (m, 2H, NCH2-CH2), 1.53-1.66 (m, 1H, NCH), 0.49-0.56 (m, 4H, NCHCH2). Anal.…”
mentioning
confidence: 99%
“…This is based on the fact that MAO-B but not MAO-A inhibitors protect against the neurotoxin MPTP which destroys dopamine nerve cells. However, there are MPTP analogs that are oxidized by MAO-A rather than MAO-B, making it equally likely that MAO-A inhibitors could play a protective role (Kindt et al, 1988;Kreuger et al, 1992).…”
Section: Discussionmentioning
confidence: 99%